The basic, the solid, the site-specific and the full or total Index of Sustainable Economic Welfare (ISEW) for Turkey - Angeliki Menegaki (Economies, 2018)
The Index of Sustainable Economic Welfare (ISEW) has been calculated in various ways for various countries and for various time spans. Based on the degree of objectivity, the Basic, Solid, and Site-specific ISEW are separated, whose sum constitutes the Total or Full ISEW. The paper proposes some guidelines for countries and smaller forms of state organizations, to apply and re-state their sustainable GDP, thus rendering it a useful figure as reported vis-à-vis the long established GDP. To demonstrate this theoretical advancement, the Turkish economy is used for an application. Turkey is a dynamic emerging economy, given its rapid GDP increase over the past two decades and the population increase on the one hand. On the other hand, it is afflicted by social inequalities and environmental problems, which if they were to be abated, they would certainly deduct from the increased income achieved so far.
Keywords: Q01; Q56; O53; 330; economic welfare; GDP; sustainability; ISEW; Turkey